(untitled) (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 55-61 to 57-63. The present investigation aimed to evaluate different fractions of P of Ganges tidal floodplain soils of Bangladesh in terms of plant availability in the selected soil. The samples were analyzed for solution P, labile pool, alkali-extracted inorganic pool, organic pool, acidic pool and residual P.The soil solution P in the tested soils ranged from 0.03 to 0.11 mg L1. The concentration of 0.5M NaHCO3 extracted P had a range of 8-34 mg kg1. Dilute NaOH extracted inorganic P had a range of 25-59 mg kg1. NaOH extracted organic P ranged from 334 to 542 mg kg1 and acid extracted P represented from 140 to 443 mg kg1, respectively. Residual P of the tested soils showed a concentration of 104-262 mg kg1. On average of the 12 soils, the relative concentration of solution P was 0.01%, NaHCO3 P was 3.2%, NaOH-Pi was 6.8%, NaOH-Po was 44.6%, acid pool was 27.3% and residual fraction was 18.1%. Different P pools showed strong correlation either with sand, silt, clay, electrical conductivity, pH(H2O), pH (KCl), organic carbon or extractable Fe content. The tested Ganges tidal floodplain soils demonstrated wide variation in the relative proportion of different P pools. Bangladesh Rice j. 2015, 19(2): 57-63